الحماية-الجنائية-للعلامة-التجارية - حليمة قلداسني; أمال بركان (My University, 2020)
Summary : Interest in the brand has increased recently. This is because it is one of the most important elements of industrial and commercial ownership and has great value as it is the means used to distinguish products from others and this protect the consumer from misinformation and increase confidence in the products offered and the services available. Some of the brands have been valued at huge amounts, such as the CocaCola brand. This value and importance of the mark made it a target for attacking it, especially through imitation. This prompted the legislative system to provide the necessary legal protection by criminalizing acts contrary to the rules of integrity and establishing deterrent penalties for those criminals whose assault on the mark constitutes an infringement of the state's economic viability and an infringement of legally protected interests. This is one of the thorny topics that has occupied the thinking of criminal law scholars and this is reflected in the many international conferences and conventions held in this field. ,,,,,,,,,,,,,,,,,,,,,, الملخص : تزايد الإهتمام بالعلامة التجارية في الأونة الأخيرة، وذلك نظرا لكونها من أهم عناصر الملكية الصناعية والتجارية ولها قيمة بالغة فهي الوسيلة المستخدمة في تمييز المنتجات عن غيرها وبالتالي تحمي المستهلك من التضليل وتزيد ثقته في المنتجات المعروضة والخدمات المتاحة ، وقد بلغت قيمة بعض العلامات مبالغ ضخمة من أمثلتها علمة كوكا كولا، هذه القيمة والأهمية للعلامة جعلت منها مستهدفة للإعتداء عليها لاسيما عن طريق التقليد، الأمر الذي دفع بالمنظومة التشريعية لتوفير الحماية القانونية اللازمة وذلك بتجريمها للأفعال المنافية لقواعد النزاهة وتقريرها لعقوبات رادعة لأولئك المجرمين الذين يشكل اعتدائهم على العلامة تعديا على المقومات الإقتصادية للدولة ومساسا بمصالح محمية قانونا، ويعتبر هذا الموضوع من المواضيع الشائكة الذي شغل فكر فقهاء القانون الجنائي ويظهر ذلك من خلال كثرة المؤتمرات الدولية والإتفاقيات التي عقدت في هذا المجال . ,,,,,,,,,,,,,,,,,,,,,,,,, Résumé : Intérêt croissant pour la marque ces derniers temps, car il est l’un des éléments les plus importants de la propriété industrielle et commerciale et a une grande valeur. C’est le moyen utilisé pour distinguer les produits des autres et ainsi protéger les consommateurs contre la tromperie et augmente leur confiance dans les produits offerts et les services disponibles; Certaines marques valent des sommes d’argent énormes, comme Coca-Cola. Cette valeur et la signification du signe en ont fait une cible d’assaut, en particulier par la tradition, Cela a conduit le système législatif à fournir la protection juridique nécessaire en criminalisant les actes contraires aux règles d’impartialité et en décidant des sanctions dissuasives pour les contrevenants dont l’agression sur la marque constitue une violation de la viabilité économique de l’État et une violation des intérêts légalement protégés. Ce sujet est considéré comme un sujet épineux qui a occupé la pensée des juristes du Code criminel et cela se reflète dans les nombreuses conférences et conventions internationales tenues dans ce domaine.